Multisensory activities to develop pre-reading skills of second basic year students at Unidad Educative Carrera Sánchez Bruno, Santa Elena province, academic year 2015-2016. - Toscano Collantes, María Alejandra (2016)
The current research is based on how to teach through activities that involve the senses and aim to help students develop pre-reading skills and prepare them for the reading process. Multisensory activities approach with the senses in different aspects and areas of thought, activating brain areas and suiting each learning style. Every child processes information differently and multisensory activities work global and are suitable for multi-level groups and students with learning disabilities such as dyslexia. The aim of this study is to show how the use of multisensory activities helps students develop their previous skills, which are useful into the reading process. The study involved the principal, English teachers and second basic year students from Unidad Educativa Carrera Sánchez Bruno and was conducted during a period of three months. Data was gathered through interviews, diagnostic test, questionnaire and post-test.